Analisis Postur Kerja Karyawan Produksi Sepatu Olahraga Menggunakan Metode Novel Ergonomic Postural Assessment pada Karyawan Ruang Produksi UD. XYZ Gresik - Dharmaji, Rizky; Dahda, Said Salim (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This research is discussed about the analysis of work posture in small-medium industries that produce sports shoes. UD XYZ Gresik is one of the companies in the athletic shoe industry that receives requests for shoes every day. Working hours for 9 hours with a break time of 1 hour. Production targets are sometimes not achieved, causing employees to work overtime. Along with the targets that must be achieved every day, employees in the shoe production room have to sit for a long time during working hours. Long working hours have an impact on musculoskeletal disorders, especially back pain. Working posture (sitting position) and length of work are factors that affect physical ability which continues to decline. Thus resulting in absenteeism and economic losses caused by a decrease in work capacity and a decrease in employee productivity. Novel Ergonomic Postural Assessment as an ergonomics method used as a tool to analyze the risk of ergonomics and working posture in the upper body to reduce the risk of musculoskeletal injuries in the production process. The results showed that the value of the first working posture was 6 (work posture needs further research and action is needed in the near future). For the second working posture, the final NERPA score was 7 (work posture needs to be checked further and action taken as soon as possible). Both of these scores require improvement due to the risk of severe musculoskeletal disorders.